Toward an Evolutionary Christian Theology - Peters, Karl E. (Zygon, 2007)
Abstract. In order to develop a single narrative of God's continuing creation that includes salvation, this essay in theological construction focuses on the idea of transformation. Using the metaphor of conceptual maps in science and religion, it weaves together ideas about evolution, God working in the world, and how humans can be brought to wholeness in community in relation to God.